Clinical practice guidelines for the diagnosis and management chronic infection of hepatitis viral C of the Peruvian Health Social Security (EsSalud) - Davalos, Milagros (2021)
Introduction: This article summarizes the clinical practice guidelines (CPG) for the diagnosis and treatment of chronic infection of hepatitis viral C of the Peruvian Health Social Security (EsSalud). Objective: To provide clinical recommendations based on evidence for the diagnosis and treatment of chronic infection of hepatitis viral C in EsSalud. Methods: A guideline development group (GDG) was established, including medical specialists and methodologists. The GDG formulated 4 clinical questions to be answered in this CPG. Systematic searches of systematic reviews and primary studies (when pertinent) were conducted in PubMed, and Central (Cochrane) during 2019. The evidence was selected to answer each of the clinical questions. The accuracy of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice and the treatment flowchart. Finally, the CPG was approved with Resolution No. 151-IETSIESSALUD-2019. Results: The present CPG addressed 4 clinical questions of four topics: screening, diagnosis, staging and treatment. Based on these questions, 13 recommendations (8 strong recommendations and 5 weak recommendations), 27 points of good clinical practice, and 1 flowchart were formulated. Conclusion: This paper summarizes the methodology and evidencebased conclusions from the CPG for for the diagnosis and treatment of chronic infection of hepatitis viral C of the EsSalud.